The Impact of Tax Burden, Firm Size, and Foreign Ownership on Transfer Pricing in Indonesia - Hanna Friska Sembiring; Fahmi Natigor Nasution; Rina br Bukit (Fakultas Ekonomi Universitas Andalas, 2025)
The present research examines how tax burden, company size, and foreign ownership influence transfer pricing decisions in manufacturing firms registered on the Indonesia Stock Exchange between 2020 and 2024. Data analysis employed a quantitative method, processed using the Eviews 13 application. This study analyzed 156 observations using unbalanced panel data regression through a fixed effect approach. The results showed that tax burden and company size significantly influenced transfer pricing decisions, while foreign ownership did not. This study revealed that transfer pricing decisions were significantly influenced by tax burden and company scale. This can be explained within the framework of agency theory, where managers attempt to minimize tax burdens to enhance the company’s performance from the owners' perspective, even though this step may lead to tension with tax authorities. In addition, this finding aligns with signaling theory, as transfer pricing practices can be viewed as a sign of management's ability to manage taxes efficiently, particularly in large companies that receive more scrutiny from external parties.